PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP KECENDERUNGAN PHUBBING PADA MAHASISWA PENDIDIKAN BAHASA ARAB SEMESTER 4 - Ila Nuroktaviani; Septi Gumiandari (ADISAM PUBLISHER, 2024)
One of the internet technologies that is currently developing rapidly and has a big influence on a person's habits is social media. The aims of this research are (1) to investigate the influence of social media on a person's attitude (2) to find out how a person uses social media (3) to find out what causes the tendency to Phubbing from social media